Emergency Neurology Oral Cases for Trainee Assessment and Education. Issue 2 (March 2019) - Loochtan, Aaron I.; Spector, Andrew R.; Sinha, Saurabh R.; Lerner, David P.
Abstract : Objectives: Neurological emergencies comprise much of neurology residency, but there may be a lack of clinical experience. For our program, oral examinations have been used to assess resident readiness for additional clinical independence. In this study, we examined the perceptions of learners and examiners of oral case examinations. Methods: Six attending physicians administered case-based oral examinations to 8 trainees. Each case involved a chief complaint and progressed through a clinical encounter. Following the examination, each attending physician and trainee completed an online 5-point Likert scale survey of content and educational value. Statistical analysis of point assignment based on Likert scale responses was performed. Results: Six attendings (100% response) and 7 trainees (87.5% response) completed the assessment. The trainees assessed all 6 cases. Residents had negative responses for 3 cases with specific concern in "feedback" and "learning experience." Residents responded with less positive response than attendings for "The case is easy to understand and progressed in a logical fashion" (3.90 for residents vs. 4.83 attendings; P =0.015) and "The case complexity is appropriate for level of training" (4.14 vs. 4.83; P =0.033). Attendings noted better understanding of trainees thought processes following oral examinations. Trainees noted feedback as the most useful component of case-based assessments. Conclusions: Case-based assessment in neurology training allows for rapid evaluation of trainees' abilities to critically think. There is general agreement from attendings and trainees that case-based assessment is a useful and positive learning tool. The responses from this survey are being used to modify the cases for future examinations. Abstract : Supplemental Digital Content is available in the text.